EJERCICIOS PARA MEJORAR LA CONDUCCIÓN DEL BALÓN DE LA SELECCIÓN DE FUTBOL EN LA UNIDAD EDUCATIVA “ADOLFO MARIA ASTUDILLO” - BRAVO ALMACHE ROBERT STEEVEN (2024)
The research was carried out at the “Adolfo María Astudillo” Educational Unit, located in Babahoyo, Los Ríos, year 2024, which aims to improve the ball handling of the institution's soccer teams. The exercises applied to perfect this skill were considered the independent variable, highlighting the importance of starting learning from an early age, driving the ball, refers to the movement of the players when interacting with the ball to gain security, was identified as the dependent variable. The investigation originated from observing that those selected from that institution had deficiencies in the synchronization and effective driving of the ball, which was proposed to address subproblems related to exercises, motivation and fundamental contents to improve this situation. This study highlights the importance of properly teaching ball driving, proposing a different approach that includes recreational activities. The objectives of the project focus on analyzing the deployment of driving, developing specific exercises and executing them, with the hypothesis that it will contribute to improving the team's performance. A type of experimental design was initiated, encompassing descriptive and explanatory approaches, using documentary methods in which qualitative and quantitative research was used to process survey data, with the aim of improving ball handling, therefore, the project seeks to improve. to the soccer team through analysis, development and execution of specific exercises. It is based on a theoretical framework that highlights the evolution of football and the importance of coaching, using a methodology that combines qualitative and quantitative approaches to obtain reliable and applicable results.